PENGARUH PEMBERIAN EKSTRAK ETANOL 90% DAUN KELOR (MORINGA OLEIFERA) TERHADAP LIBIDO TIKUS JANTAN - CHAIRIYAH ATIQAH PUTRI; MELVIANA LUBIS (JURNAL ILMIAH KOHESI, 2023)
Sexual dysfunction is a disorder of sexual function, a lack of desire or no urge to have sexual activity. Subjectively, sexualDysfunction is the absence or reduced sexual desire from any kind of sexual stimulation. One type of sexual dysfunction islow-sex drive (libido). Decreased libido includes sexual dysfunction, where there is a decrease in testosterone levels, so thatIt can lead to a decrease or loss of a person's sexual desire. Libido treatment can use herbal plants that are aphrodisiac, namelyplants that function to increase a person's libido. The moringa plant (Moringa oleifera) is a plant that has many benefits that haveeconomic value as well as health benefits, so many people cultivate this plant because the skin, stems, leaves, fruit, andseeds can be utilized. This Moringa plant has several nicknames, such as Tree for Life, The Miracle Tree, and Amazing Tree.This research aims to determine the effect of giving 90% ethanol extract of Moringa (Moringa oleifera) leaves onlibido in male rats at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW. This study is a true experimental study witha post-test controlled group design, which is a type of research that observes the control group and the treatment group afterthe action, where in this study there are 1 control and 3 groups with different treatment doses. There was no significantdifference in the administration of 90% ethanol extract of Moringa (Moringa oleifera) leaves to the mounting frequency ofmale rats in each test group, with a significance value obtained of 0.248 (p > 0.05). There is no significant effect of giving 90%ethanol extract of Moringa leaves (Moringa oleifera) to increase libido in male rats